2021
DOI: 10.1186/s41235-021-00291-4
|View full text |Cite
|
Sign up to set email alerts
|

Improving college students’ fact-checking strategies through lateral reading instruction in a general education civics course

Abstract: College students lack fact-checking skills, which may lead them to accept information at face value. We report findings from an institution participating in the Digital Polarization Initiative (DPI), a national effort to teach students lateral reading strategies used by expert fact-checkers to verify online information. Lateral reading requires users to leave the information (website) to find out whether someone has already fact-checked the claim, identify the original source, or learn more about the individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 37 publications
2
38
1
2
Order By: Relevance
“…Guess et al (2020) found that a brief intervention aimed at teaching people how to spot fake news significantly improved the ability to tell truth from falsehood, but not sharing intentions, in both American and Indian samples, and Epstein et al (2021) found that an even briefer version of the same intervention improved the quality of COVID-19 news Americans indicated they would share online (although this improvement was no greater than the improvement from simply priming the concept of accuracy). Relatedly, McGrew et al (2019), Breakstone et al (2021) and Brodsky et al (2021) found that much more extensive fact-checking training modules focused on lateral reading improved students' assessments of source and information credibility. These interventions were focused more on media literacy than on digital skills per se; and similarly, Hameleers (2020) found that a media literacy intervention with no digital literacy component increased American and Dutch subjects' ability to identify misinformation.…”
Section: Discussionmentioning
confidence: 95%
“…Guess et al (2020) found that a brief intervention aimed at teaching people how to spot fake news significantly improved the ability to tell truth from falsehood, but not sharing intentions, in both American and Indian samples, and Epstein et al (2021) found that an even briefer version of the same intervention improved the quality of COVID-19 news Americans indicated they would share online (although this improvement was no greater than the improvement from simply priming the concept of accuracy). Relatedly, McGrew et al (2019), Breakstone et al (2021) and Brodsky et al (2021) found that much more extensive fact-checking training modules focused on lateral reading improved students' assessments of source and information credibility. These interventions were focused more on media literacy than on digital skills per se; and similarly, Hameleers (2020) found that a media literacy intervention with no digital literacy component increased American and Dutch subjects' ability to identify misinformation.…”
Section: Discussionmentioning
confidence: 95%
“…Another action could involve the design of forms on advanced reading comprehension strategies, such as the case of checklists or others (Mohamadi, 2018;Yunusa and Umar, 2021). Finally, the implementation of online records and protocols for the instruction and cross-sectional evaluation of advanced reading comprehension and other generic and specific competences, as has been done with the citizen with lateral reading and checking fakes while reading information from various subjects and fields (Brodsky et al, 2021;Cabrera et al, 2021;Fandiño-Parra et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…(García and García-Martín, 2021a,b;Graham, 2021;López et al, 2021;Robledo-Ramón and García-Gutiérrez, 2021). The same happens with citizen competence, where critical thinking represents 70% of the assessment of competence, which implies the resolution of citizen problems, which require a high dose of advanced reading comprehension, as in the case of the development of lateral reading strategies and contrast of facts in the face of hoaxes and fakes (Brodsky et al, 2021;Cabrera et al, 2021). It is evident that advanced reading comprehension plays a role in generic quantitative reasoning competence.…”
Section: Introductionmentioning
confidence: 99%
“…2015; Koster et al, 2015;Robledo y García, 2018). En este sentido, estudios recientes sobre la competencia ciudadana en entornos internacionales diversos y específicos latinoamericanos, por ejemplo, ilustran la necesidad de trabajar la comprensión lectora con estrategias de contraste de hechos, o de lectura lateral, y que requieren grandes dosis de pensamiento crítico y que se evidencia con la necesidad de alto dominio de CLA (Brodsky et al, 2021;Cabrera et al, 2021;Fandiño-Parra et al, 2021).…”
Section: Conclusionesunclassified